Effect of chemical modification of silica surface with metal oxides on the thermal properties of adsorbed polydimethylsiloxane - Borysenko, M.V.; Bogatyrov, V.M.; Dyachenko, A.G.; Pokrovskiy, V.A. (Поверхность, 2002)
Temperature programmed desorption mass spectrometry, thermogravimetry and differential thermal analysis were used to investigate the thermal destruction of adsorbed polydimethylsiloxane (PDMS) in air and vacuum conditions. Fumed silicas, whose surface contained grafted oxygen compounds of metals or phosphorus, were used as adsorbents. VOCl₃, CrO₂Cl₂, TiCl₄, SnCl₄, AlCl₃, PCl₃ and Zn(Acac)₂ vapors were applied as modifiers. It was found that in air the presence of metal oxides and phosphorus on silica surface lead to partial depolymerization of adsorbed PDMS. Degree of depolymerization ranges up to about 80% for V/SiO₂, P/SiO₂ and Al/SiO₂ samples containing 40% PDMS. The presence of metal oxides on silica surface decrease of starting temperatures of Si-C bond destruction in vacuum and result in elimination of methane at 140-550 and 550-850°С.